Motivational interviewing may resolve vaccine hesitancy - Scott L. Baughan (Clinical Research In Practice: The Journal of Team Hippocrates, 2023)
A clinical decision report using: Gagneur A, Lemaître T, Gosselin V, et al. A postpartum vaccination promotion intervention using motivational interviewing techniques improves short-term vaccine coverage: PromoVac study. BMC public health. 2018;18(1):811. https://doi.org/10.1186/s12889-018-5724-y for a juvenile patient with a caregiver who is skeptical about the safety of routine vaccinations.